The Montevideo Treaty and Latin American economic integration - WIONCZEK, M.S. (PSL Quarterly Review, 2014)
Despite its brevity, the Montevideo Treaty establishing the Latin American Free Trade Association is a rather far-reaching legal instrument for the seven participating countries. It embodies not only provisions for gradual trade liberalization within the area, but also establishes a basic, albeit sketchy, structure of a regional economic integration programme. The present article first reviews the provisions of the treaty before looking at the developments that led to its birth. The ECLA-sponsored common market plan is then considered as well as the project for Southern Latin America. The diametrically opposed views of the GATT and the IMF are then examined. Finally, the integration efforts between the United States and Latin America are analysed. The author concludes by considering the future of the Montevideo Treaty. JEL: F13, F15, F33